Corak Pemikiran Cendekiawan Muslim dalam Merespon Persinggungan Islam dan Modernitas - Zahra, Fathimatuz; Hakim, M. Nasrul; Arifin, Zainul; al-Hasyimi, Sholahuddin (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
Islam, science, and colonialism have continuing problems over time. To understand the point that makes this intersection suffer a deadlock, mainly with Islam. The intersection of modernity and colonialism gave birth to many Islamic thinkers who also tried to formulate how Islam stands when confronted with modernity, science, and colonism. This article complements articles related to the intersection of Islam, science, and modernity of various early Muslim thinkers. This article re-examines the confusion because, to this day, the fundamental problems of the intersection of Islam, science, and modernity are increasingly experienced in the digital age. The findings in this article on the intersection of Islam and modernity impact Islam, science, and colonialism. This impact is present in the form of various rejections of Islamic scientists of the existence of modernity, mainly in science. The emergence of various rejection movements related to this advance of science makes it seem that Islam itself is unable to meet the challenges of the age. In addition to the colonialism perspective that reinforces that colonism is embodied in colonization in the domination of science today. This has an impact on the total disbelief of the Muslims in the advancement of science and technology.